Chloroplast DNA Copy Number May Link to Sex Determination in Leucadendron (Proteaceae) - MADE PHARMAWATI; GUIJUN YAN; PATRICK FINNEGAN (HAYATI Journal of Biosciences, 2009)
Leucadendron (Proteaceae) is a South African genus, the flowers of which have become a popular item in the Australian cut-flower industry. All species are dioecious. In general the female flowers are the more desirable as cut flowers. The availability of a molecular marker linked to sex determination is therefore needed both to maximize the efficiency of breeding programs and to supply markets with flowers from the preferred sex. The polymerase chain reaction-based method of suppression subtractive hybridization (SSH) combined with mirror orientation selection (MOS) were applied in an attempt to identify genome differences between male and female plants of Leucadendron discolor. Screening of 416 clones from a male-subtracted genomic DNA library and 282 clones from a female-subtracted library identified 13 candidates for male-specific genomic fragments. Sequence analyses of the 13 candidate DNA fragments showed that they were fragments of the chloroplast DNA, raising the possibility that chloroplast DNA copy number is linked to sex determination in Leucadendron. Key words: Leucadendron, sex determination, suppression subtractive hybridization (SSH)